2009
DOI: 10.1128/jvi.01824-08
|View full text |Cite
|
Sign up to set email alerts
|

Peptidylproline cis - trans -Isomerase Pin1 Interacts with Human T-Cell Leukemia Virus Type 1 Tax and Modulates Its Activation of NF-κB

Abstract: Human T-cell leukemia virus type 1 (HTLV-1) is an oncogenic retrovirus etiologically causal of adult T-cell leukemia (ATL). The virus encodes a Tax oncoprotein that functions in transcriptional regulation, cell cycle control, and transformation. ATL is a highly virulent cancer that is resistant to chemotherapeutic treatments. To understand this disease better, it is important to comprehend how HTLV-1 promotes cellular growth and survival. Tax activation of NF-B is important for the proliferation and transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 73 publications
1
41
0
Order By: Relevance
“…Ubiquitination, sumoylation, acetylation, and phosphorylation of Tax have been shown to influence its transcriptional function (5,9,22,23,25,28,34,35,40). Tax ubiquitination has been reported to be required for its activation of NF-B, and it has been found that the Tax-polyubiquitin chains are predominantly K63 linked (40).…”
Section: Resultsmentioning
confidence: 99%
“…Ubiquitination, sumoylation, acetylation, and phosphorylation of Tax have been shown to influence its transcriptional function (5,9,22,23,25,28,34,35,40). Tax ubiquitination has been reported to be required for its activation of NF-B, and it has been found that the Tax-polyubiquitin chains are predominantly K63 linked (40).…”
Section: Resultsmentioning
confidence: 99%
“…Among candidate genes, we selected and characterized the gene encoding Pin1, because it has been implicated in many viral infections, including human immunodeficiency virus (HIV) replication (29), HBV-mediated hepatocarcinogenesis (17), and human T cell leukemia virus type 1 (HTLV-1) malignant transformation (7,20). Silencing of Pin1 expression led to strong inhibition of HCV production (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It interacts with hepatitis B virus X protein to enhance hepatocarcinogenesis (17). Pin1 stabilizes human T cell leukemia virus type 1 (HTLV-1) Tax oncoprotein and promotes malignant transformation (7,20). Pin1 also modulates the replication of human immunodeficiency virus type 1 (HIV-1) via interaction with APOBEC3G protein (29).…”
Section: Discussionmentioning
confidence: 99%
“…Expression vectors for TCF1, LEF1, and Tax were described (16,45). Flag-CREB was made by subcloning the CREB coding sequence into pCAGFlag.…”
Section: Methodsmentioning
confidence: 99%